(untitled) (PlaySpace, 2023)
In the 20th century a wave of experimentation and discussion hit most artistic disciplines. As pianist-researcher Mine Dogantan-Dack points out, classical music has been slow to join in. Although composers have been experimenting with the musical language, classical music performance as an artistic practice has relatively stayed untouched. In the area of vocal music, the traditional recital format with the singer standing by the piano is THE standard. In my doctoral research project, I aim to challenge and explore alternatives to this traditional format. I start by investigating the original performance practice of Satie’s mélodies to then design three different performances of this repertoire using various artistic methods and theoretic concepts. The first one is based on the approach known as historical informed performance (HIP). Satie’s mélodies are little known and seldom performed. They are also difficult to appreciate at a first hearing: incredibly short, condensed in their simplicity, lacking catchy melodies and with obscure texts. My hypothesis is that the standard way of performing them, as a static vocal chamber music recital, doesn’t suit them and makes it in fact harder for the public to appreciate them. Investigating the original performance practice then became a way to rediscover other aspects of the music, beyond the dogmas of the score, and to find inspiration for creating alternative modes of presenting classical vocal chamber music. In this paper I retrace my use of HIP as a creative tool for designing performances of classical music.